University as stimulus to promote intention to separate food waste: a study on the Chinese female residential students - Pick-Soon Ling; Jia Yi; Shi Yee Wong (Cogent Business & Management, 2024)
Overwhelming food waste impacted society and the environment. One of the initiatives to mitigate this problem is to separate the food waste and utilise it for alternative purposes. However, few studies have examined universities' role in separating female residential students' food waste, even though universities contribute to food waste generation. Therefore, this study investigates the university's role on this matter. Through purposive sampling, 339 responses from female residential students were gathered and analysed using the Partial-Least-Square-Structure Equation Modelling (PLS-SEM) and Importance-Performance Map Analysis (IPMA) techniques. The results revealed that the university environment (UE) and university policy regulation (UPR) influenced female residential students' attitudes (ATT) toward food waste separation. In contrast, UPR and ATT significantly influenced the students' food waste separation intention (FWSI). The mediation analysis also showed the significance of the UE and UPR, which could indirectly affect the students' FWSI through ATT. Furthermore, the Importance-Performance Map Analysis (IPMA) showed that the improvement effort should be more focused on ATT as the current performance is low. Thus, the importance of the university-related factors was provided in this study. The finding is expected to bring theoretical and practical advantages.
Keywords: 650; Chinese university students; Female residential students; Food waste separation; Partial Least Square-Structure Equation Modelling; Stimulus-organism-response; University environment; University policy regulation